Ecological Education in Waste Management as a Tool for The Implementation of Sustainable Development - Pawul, Małgorzata; Sobczyk, Wiktoria (Problemy Ekorozwoju, 2011)
A big amount of communal waste is a problem that occurs in many urban areas of the European Union. In its solution dynamic technological development in utilization and reuse of waste is a propitious factor. To make this actions fully successful – and coherent with sustainable development principle – it must be associated with increase of environmental awareness which leads to involvement of local communities in segregation and correct waste management. The article presents examples of ecological education and waste management in selected European countries: Germany, Finland, Belgium, Great Britain and Poland.